The role of nutraceuticals of natural origin in the treatment of depressive disorders - Sęk, Michał; Galasińska, Iwona; Hajduk-Maślak, Katarzyna; Michalik, Beniamin; Skóra, Adrianna; Zając, Dominik (Journal of Education, Health and Sport, 2025)
Introduction: Major Depressive Disorder is a prevalent mental disorder, significantly contributing to the number of disability-adjusted life years and years of healthy life lost to disability. The efficacy of currently available treatment modalities is limited by adverse effects and suboptimal treatment response, highlighting the need for additional therapeutic options. A growing body of evidence suggests that numerous nutraceuticals of natural origin may be implemented in the treatment of depression. Aim of the study: The aim of the study was to compile and analyze current literature regarding the supplementation with polyunsaturated fatty acids, probiotics, polyphenolic antioxidants, vitamins and minerals in treatment and prevention of depression, both as an adjunct to antidepressants and as a standalone therapy. Methods and materials: A literature search was conducted using the PubMed database and Google Scholar, focusing on recent publications, primarily from the past 10 years. Additionally, references from selected articles were included in the analysis. Summary: Recent scientific literature suggests that all analyzed nutraceuticals may be effectively used in the treatment of depression. However, further research, particularly large-scale randomized controlled studies, is crucial to confirm the efficacy of these compounds as treatment modalities.